Living in a Sober Living House: Conversations with Residents. (7th February 2022) - Davis, Jennifer; Berman, Jake
Abstract: Background : Twenty-one residents in a sober living facility in a medium sized Midwestern city were interviewed and were asked to talk about their experiences in selecting and residing in a sober living facility. Methods : Respondents were also asked to detail their thoughts about the efficacy of sober living and their ideas about successful recovery. Interviews were semi-structured in order to provide opportunity for in-depth responses. Results : Based on an analysis of the interview transcripts the following themes were presented for analysis and discussion: The role of early trauma, the strengths of sober living, the challenges to sober living and keys to sobriety. Discussion : Discussion of contradictions between present findings and the literature as well as recommendations for future research and practice are presented.